BLOCKCHAIN APPLICATIONS BEYOND CRYPTOVALUTA: A LITERATURE PERSPECTIVE ON THE USE OF BLOCKCHAIN TECHNOLOGY - Loso Judijanto; Al-Amin (CV. Adiba Aisha Amira, 2024)
Blockchain applications beyond cryptovaluta make it clear that this technology has a wide range of promising applications in various industry sectors. Blockchain is known for its decentralised, transparent, and secure nature, so its use can improve operational efficiency and reduce the risk of fraud. The study highlights various implementations of blockchain such as in supply chain management, where the technology can ensure authenticity and smooth flow of goods, as well as in healthcare systems that enable secure storage and exchange of patient data. However, the adoption of blockchain technology also faces obstacles such as immature regulations, challenges in compatibility between systems, and cost and technical complexity. Further research and infrastructure support are needed to overcome these barriers. Despite these challenges, blockchain's potential advantages make it one of the key innovations that has the opportunity to redefine the way various industries operate in the future.